Students’ Difficulties in Speaking English - Jannah, Wirda Jannatul; Niati, Batdal (JEE (Journal of English Education), 2022)
The purpose of this research was to find out students’ difficulties in speaking English skill. This research use descriptive qualitative research design. While the writer described and students’ difficulties in speaking skill. The population of his research was taken rom the fourth semester students’ English department University of PasirPengaraian. This class consisted 0f 26 students. Based on the data of analysis, it can be concluded that the fourth semester students’ English department University o f PasirPengaraian in students’ difficulties speaking most was they lack necessary of vocabulary and at least was students tend to use "Native" language when they are speaking English.